Examining the association between cultural self-construal and dream structures in the United States and Japan - Konakawa, Hisae; Kawai, Toshio; Tanaka, Yasuhiro; Hatanaka, Chihiro; Bowen, Kimberly; Koh, Alethea (Frontiers in Psychology, 2023)
Cultural differences in self-construal, human relationships and values between Western and East Asian people have been suggested. The aim of this article is to investigate cultural difference in dreamers’ self-construal based on their dreams, by studying the dreams sampled via online questionnaires from 300 non-clinical participants from America and Japan respectively. The current results revealed the prevalence of the independent view of self in American participants and the interdependent view of self in Japanese participants. In addition, we found significant cultural differences in the dream length and structural patterns. For American dreams, the dream-ego had a clear will and strong mobility, and there were obvious ends of dream events. Conversely, for Japanese dreams, the weak agency and vague conscious of the dream-ego were shown, and others could play a main role in one’s dreams. These characteristics may be influenced by the differences in self-construal or in the process of self-formation between American and Japanese cultures.